Role of ErbB and IL-1 signaling pathways in the dermonecrotic lesion induced by Loxosceles sphingomyelinases D - Pinto, Bruna Fernandes; Lopes, Priscila Hess; Trufen, Carlos Eduardo Madureira; Ching, Ana Tung Ching; De Azevedo, Inácio de Loiola Meirelles Junqueira; Nishiyama, Milton Yutaka; Pohl, Paula Cristiane; Tambourgi, Denise V (Archives of toxicology, 2023)
Sphingomyelinase D (SMase D), the main toxic component of Loxosceles venom, has a well-documented role on dermonecrotic lesion triggered by envenomation with these species; however, the intracellular mechanisms involved in this event are still poorly known. Through differential transcriptomics of human keratinocytes treated with L. laeta or L. intermedia SMases D, we identified 323 DEGs, common to both treatments, as well as upregulation of molecules involved in the IL-1 and ErbB signaling. Since these pathways are related to inflammation and wound healing, respectively, we investigated the relative expression of some molecules related to these pathways by RT-qPCR and observed different expression profiles over time. Although, after 24 h of treatment, both SMases D induced similar modulation of these pathways in keratinocytes, L. intermedia SMase D induced earlier modulation compared to L. laeta SMase D treatment. Positive expression correlations of the molecules involved in the IL-1 signaling were also observed after SMases D treatment, confirming their inflammatory action. In addition, we detected higher relative expression of the inhibitor of the ErbB signaling pathway, ERRFI1, and positive correlations between this molecule and pro-inflammatory mediators after SMases D treatment. Thus, herein, we describe the cell pathways related to the exacerbation of inflammation and to the failure of the wound healing, highlighting the contribution of the IL-1 signaling pathway and the ERRFI1 for the development of cutaneous loxoscelism.
Keywords: pavoučí jedy; Sphingomyelin Phosphodiesterase; signální transdukce; pavouci; Signal Transduction; kousnutí pavoukem; Humans; sfingomyelinfosfodiesterasa; ErbB Receptors; Phosphoric Diester Hydrolases; Spider Venoms; Inflammation; lidé; zvířata; zánět; erbB receptory; fosfodiesterasy; Spiders; Spider Bites; Animals; Interleukin-1; interleukin-1